2023
DOI: 10.7324/jabb.2023.11504
|View full text |Cite
|
Sign up to set email alerts
|

A review on the biological properties of Trichoderma spp. as a prospective biocontrol agent and biofertilizer

Abstract: The over-use of synthetic pesticides and fertilizers has resulted in favoring the selection of resistant plant pathogens and the reduction of soil fertility. Eco-friendly alternatives such as the use of biocontrol agents and biofertilizers should be practiced as substitutes to the synthetic chemicals in this present day. The use of fungi such as Trichoderma species as biocontrol agents has been widely practiced in forestry and industrial agriculture. Biocontrol agents are effective against many pathogenic fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Nevertheless, it would be necessary to monitor this over a longer period of time in order to see whether there is competition and the possible overgrowth of any of the species of microorganism. The experiment was conducted in an indoor vertical growing system in the Future Farming Ltd. R&D centre (Kaly 66, 49.3792886 N, 16.3515736 E, Czechia). The growing…”
Section: Biofilter Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, it would be necessary to monitor this over a longer period of time in order to see whether there is competition and the possible overgrowth of any of the species of microorganism. The experiment was conducted in an indoor vertical growing system in the Future Farming Ltd. R&D centre (Kaly 66, 49.3792886 N, 16.3515736 E, Czechia). The growing…”
Section: Biofilter Experimentsmentioning
confidence: 99%
“…The experiment was conducted in an indoor vertical growing system in the Future Farming Ltd. R&D centre (Kaly 66, 49.3792886 N, 16.3515736 E, Czechia). The growing system consisted of four racks, where plants were cultivated through a deep-water culture (DWC) technique.…”
Section: System Setup and Cultivation Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trichoderma, known for its remarkable adaptive capacity to diverse environmental conditions, has emerged as a promising source of metabolites and biocontrollers (Sandle, 2014). These alternatives offer effective pest and pathogen control and align with the principles of environmentally friendly and sustainable agriculture (Abdul-Halim et al, 2023). In practical terms, research has demonstrated the inhibitory activity of Trichoderma species, particularly Trichoderma asperellum and Trichoderma atroviride, against various pathogens such as Fusarium and Aspergillus.…”
Section: Overview Of Trichoderma Sppmentioning
confidence: 99%